'Hey everybody, don't get pregnant': Zika, WHO and an ethical framework for advising. Issue 5 (5th December 2016) - Byron, Katie; Howard, Dana
Abstract : WHO recently issued new guidance on the prevention of sexual transmission of Zika virus. The updated guidance states that '[c]ountry health programmes should ensure that… [i]n order to prevent adverse pregnancy and fetal outcomes, men and women of reproductive age, living in areas where local transmission of Zika virus is known to occur, be correctly informed and oriented to consider delaying pregnancy'. While the media has reported this advice as WHO telling couples in Zika-affected regions to avoid pregnancy, WHO states that they are not doing that. In an interview with the New York Times, a spokesperson from WHO stated, 'it's important to understand that this is not WHO saying, "Hey everybody, don't get pregnant." It's that they should be advised about this, so they themselves can make the final decision'. In this statement, the WHO's spokesperson distinguishes between actively directing individuals to delay pregnancy and advising them, which is portrayed as a merely informative act that facilitates but does not direct an individual's final decision. This paper proposes that advising should not be understood as a purely informational and non-directive act. The choices that agencies make in what advice to offer and to whom to offer the advice are ethical choices with practical implications. We will thus lay out a framework for considering the ethical issues that arise in the context of advising and demonstrate how it can be used to evaluate the WHO guidance.